Invertebrados del Cenozoico de la Argentina - del Río, Claudia Julia (2007)
The Cenozoic rocks of Argentina contain a rich, exceptionally well preserved and remarkable diverse marine and continental invertebrate fauna. The main goal of the present synthesis consists in revealing the continuous progress of the scientific research performed during the last 50 years dealing with these assemblages. Initial studies of microfaunas were carried out between the 50? and 60? and since then the interest for forams and ostracods experimented a marked increase among workers. Analysis on these faunas not only improved the knowledge of their taxonomic composition, provided a proper frame for biostratigraphic works for accurating age assignments of Argentinean Cenozoic strata, but also became a new source of data to be used in paleoenvironmental interpretations. Although known since the middle part of the XIX century, during the last five decades, macroinvertebrates have been matter of a renewed interest by paleontologists. Being the most abundant, the Tertiary marine shallow- water molluscs are the group that most noticeable drew the attention of researchers, and a large part of the investigations focused to clarify systematic aspects that led to meaningful comparisons with other Southern Hemisphere and Caribbean assemblages. Nevertheless, though a large amount of work has been already done, these assemblages are in need of a comprehensive revision in order to accomplish the proper information to make any final inferences involving origin of these faunas, as well as their biogeographic and paleoclimatic implications. Several Tertiary groups (braquiopods, equinoids, bryozoans and corals) still remains poorly understood, and only arthropods were subject of study by scientists during this last decade. By the way, Cenozoic continental molluscs have been recently receiving attention after that many years elapsed since the pioneer studies.